Communication at the health care coalface: lessons from selected clinics in Port Elizabeth - Mbengo, Nomatshawe (Rhodes University, Faculty of Humanities, School of Languages, 2012)
This thesis analyses the state of health care in South Africa with particular reference to a clinic and the Provincial Hospital in Port Elizabeth, Eastern Cape. The complexities of health care provision in a diverse sociolinguistic environment where certain languages are emphasized over others, forms the cornerstone of the research. The research focuses on health care in a complex multi-cultural environment. The goal of the research is to present a coherent and robust translation framework for the development of suitable materials to enhance communication across language and cultural barriers in the health care sector. A model (based on research completed in the USA) is presented as a possible alternative in the final chapter of the thesis.
Keywords: Communication in medicine -- Research -- South Africa; Community health services -- South Africa -- Eastern Cape; Social medicine -- Research -- South Africa; Medical care -- Research -- South Africa